Valorization of Carrot Pomace: UVC Induced Accumulation of Antioxidant Phenolic Compounds - Juan Carlos Sánchez-Rangel (MDPI AG, 2021)
Carrot pomace is the main waste residue obtained during carrot juice extraction. Plant tissues respond to abiotic stresses (i.e., wounding stress and ultraviolet C (UVC) radiation) by accumulating bioactive compounds. Due to the mechanical damage occurring during juice extraction, carrot pomace undergoes extreme wounding stress. In this study, the effects of UVC light (11.8 W m−2, 0–120 min) and storage time (48 h, 25 °C) on the accumulation of phenolics compounds and the antioxidant activity (AOX) of carrot pomace were evaluated. Carrot pomace that was non-treated with UVC (control) showed a 709.5% increase in total phenolics at 48 h. A high correlation of AOX values against total phenolics (R2 = 0.87) was observed, indicating that phenolics were the main contributors to the AOX of the tissue. After UVC treatment, the pomace that was radiated for 120 min with UVC showed an increase (40.4%) in chlorogenic acid (CHA) content. At 24 h, protocatechuic acid and 3,5-dicaffeoylquinic acid, which were not detected before storage, showed accumulation by 166.5 mg/kg and 169.4 mg/kg, respectively, in UVC treated pomace. Chlorogenic acid showed the highest increase (143.6%) at 48 h in the control. Valorization of carrot pomace was achieved by increasing its concentration of antioxidant phenolics through UVC radiation.